Multidimensional analyses of streetism based on recent evidence from urban cities in southwestern Nigeria: key indicators, causes and perceived age-long interventions (2024)
Streetism is a phenomenon where children, typically under the age of 18, live and, or work on the streets, often without adult supervision or guardianship. This study, through multidimensional approach (OUAN, qual and document analysis), streetism based on recent evidence from urban cities in southwestern Nigeria. The study assessed key indicators, causes and perceived age-long interventions to streetism. Document analysis examined were from veritable sources such as Google scholar, Scopus, and African Journals Online (AJOL). The population comprised all stakeholders across various divides such as religion, occupation, community, law enforcement agencies, marketplaces, basic schools, and families. Purposive technique was used to select 530participants from six capital cities in southwestern Nigeria. Data were collected and analysed using descriptive statistics and thematic analysis. Findings revealed top three indicators of streetism to include negative past experiences, abandonment/neglect and rural-urban migration were rated as critical causes of streetism. Also, top three rated perceived age-long intervention were allocation of specific funds, social worker roles and adoption of vulnerable children. Qualitative result showed that several street children in the region have limited or no access to formal schooling, with barriers such as lack of documentation, school fees, and transportation costs hindering their enrollment and attendance. The implications of the findings were also discussed. It is recommended that concerted efforts must be made to improve access to education, social services, family support, and economic opportunities, as well as initiatives to combat poverty, promote child welfare, and strengthen child protection systems.